Pengembangan Buklet Sebagai Media Pendidikan Kesehatan Reproduksi Pada Remaja Cacat Netra - Ghazali, Pariawan Lutfi (Faculty of Medicine, Universitas Islam Indonesia, 2009)
Reproductive health education is crucial for blind adolescent, because physiologically blind adolescent experience normal development of reproductive system, function, and process. Booklet is chosen as a media for reproductive health education for blind adolescent, because it is a printed media that can accommodate text and pictures in large amount, and considering that Braille letters take 1½ - 2 times larger space compared with usual letters. This study aims to develop booklet as a reproductive health education media for blind adolescent. The research was done using qualitative method in Resource Center IX DIY and Yayasan Kesejahteraan Tuna Netra Islam (Yaketunis) Yogyakarta. The subjects of this study were the practitioners of education printed media for blind people, teachers of blind adolescent, and blind adolescent. The instrument of this research included in-depth interview guidelines, FGD (focus group discussion) guidelines, and booklet blueprint. The booklet development included determining the objectives –which is increasing the adolescent’s reproductive health knowledge-, arranging the materials of reproductive health for booklet, and determining the basic commodities for booklet. The basic commodities used in making this booklet are 160 grams HVS paper sized 11.5 X 12 inch2 for text and 0.15 cm mica plastic for pictures. The 3-dimension forms of human reproductive organs were illustrated by two to three 2-dimension pictures from different perspectives. Texts were printed using Braille printer and pictures made of thermoform. The booklet consist of 27 pages with Rp. 48.000,00 constant cost and Rp13.750,00 variable cost. From this research, it can be concluded that booklet is developable as education media of reproductive health for blind adolescent. The basic commodities used are 160 grams HVS paper sized 11.5 X 12 inch2 and 0.15 mm mica plastic.Keyword: booklet, reproductive health, blind adolescent